2011
DOI: 10.1016/j.humov.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Center-of-pressure regularity as a marker for attentional investment in postural control: A comparison between sitting and standing postures

Abstract: Postural control is a highly automatized basic activity that requires limited attentional investments. These investments have been shown to increase from balancing experts to controls, and from controls to persons with impaired postural control. Such between-subject comparisons led to a proposed direct relation between the regularity of center-of-pressure (COP) fluctuations and the amount of attention invested in posture. This study aims to expand this relation to a within-subject comparison of conditions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(187 citation statements)
references
References 38 publications
6
179
1
1
Order By: Relevance
“…These measures were chosen because each was thought to describe a unique property related to postural control. Specifically, EA was thought to describe the size of area in which postural sway takes place (McKeon et al 2008;Prieto et al 1996), PL to provide information about the overall amount of postural sway (Roerdink et al 2010), PL n to describe the degree of twisting and turning in sway coordination (Donker et al 2007(Donker et al , 2008Roerdink et al 2010), and SEn to indicate the degree of temporal complexity (or predictability) in postural sway (Richman and Moorman 2000;Roerdink et al 2006). In short, the set of measures chosen was used to quantify aspects of both the magnitude (PL and EA) and structure (PL n and SEn) of postural sway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measures were chosen because each was thought to describe a unique property related to postural control. Specifically, EA was thought to describe the size of area in which postural sway takes place (McKeon et al 2008;Prieto et al 1996), PL to provide information about the overall amount of postural sway (Roerdink et al 2010), PL n to describe the degree of twisting and turning in sway coordination (Donker et al 2007(Donker et al , 2008Roerdink et al 2010), and SEn to indicate the degree of temporal complexity (or predictability) in postural sway (Richman and Moorman 2000;Roerdink et al 2006). In short, the set of measures chosen was used to quantify aspects of both the magnitude (PL and EA) and structure (PL n and SEn) of postural sway.…”
Section: Introductionmentioning
confidence: 99%
“…This has led researchers to hypothesize that healthy and/or more expert-like postural sway may contain a certain amount of 'noise' or 'variability' within its temporal structure that might reflect flexibility, adaptability, automaticity, or even exploratory postural control. Conversely, a less complex sway has been interpreted to reflect a more rigid, less adaptable, and possibly more attention-demanding postural control (Donker et al 2007(Donker et al , 2008Newell 1997;Pellecchia et al 2005;Roerdink et al 2010;Schmit et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous research has shown small differences in SampEn to be clinically meaningful. 31,40 For example, Donker et al 29 observed a difference in SampEn of 0.3 in a study comparing normally developing children and children with cerebral palsy. As a peripheral nervous system pathology, CAI may have less of an effect on postural control dynamics and thus on SampEn.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, COP registrations are often complemented with EMG measures and/or measures of cortical activity, allowing a better understanding of how intermuscular coordination of balance is regulated [17][18][19][20][21]. Also direct and indirect measures of the attentional investment in postural control are often used, such as stimulus-response reaction times or the regularity of COP excursions [10,[22][23][24][25]. For example, if human subjects do indeed adopt an attentiondemanding stiffness strategy when instructed to stand as still as possible, as suggested by Bonnet [1], this should be evident in higher co-contraction, greater cortical (prefrontal) activity, longer stimulus-response reaction times and more regular COP excursions compared to a neutral control instruction.…”
Section: Dv: Natural Postural Control Is More Than Just the Amount Ofmentioning
confidence: 99%